2014
DOI: 10.1111/j.1532-950x.2014.12090.x
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐Isometric Points for the Technique of Lateral Suture Placement in the Feline Stifle Joint

Abstract: Ff-Tt provides the best quasi-isometric points for placement of lateral sutures in cats, compared with all combinations tested. Further assessments with biomechanical studies are needed to evaluate the reproducibility of these landmarks for stabilization of CCL rupture in cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In that study, no correlation was made between quasiisometric points and stifle joint stability. In the present study, three different arrangements of lateral sutures were tested and the results showed similar behaviour in the cranio-caudal direction, but not in the proximo-distal direction where the two techniques with insertion points distal to the most quasi-isometric points previously reported resulted in significant differences when compared to the intact cranial cruciate ligament (12).…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…In that study, no correlation was made between quasiisometric points and stifle joint stability. In the present study, three different arrangements of lateral sutures were tested and the results showed similar behaviour in the cranio-caudal direction, but not in the proximo-distal direction where the two techniques with insertion points distal to the most quasi-isometric points previously reported resulted in significant differences when compared to the intact cranial cruciate ligament (12).…”
Section: Discussionmentioning
confidence: 55%
“…Fabello-tibial sutures remain the most commonly accepted method of stabilization for the cranial cruciate ligament rupture in the feline stifle, and several codependant factors have been identified that contribute to the success of this surgical technique (9). Despite the popularity of quasi-isometric points for the placement of fabella-lateral sutures in dogs and cats, there are few biomechanical studies that compare different anchorage points in the lateral stifle joint through the range-ofmotion (12)(13)(14)(25)(26)(27)(28)(29)(30). In a recent feline cadaveric study, paired points located between the centre of the fabella and proxi-mo-cranial tibia provided the most quasiisometric points for the placement of a fabella-tibial suture (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations